1997
DOI: 10.1002/(sici)1097-0142(19971015)80:8<1489::aid-cncr17>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the tumor necrosis factor-? promotor region and in the heat shock protein 70 genes associated with malignant tumors

Abstract: METHODS.The authors used an allele specific polymerase chain reaction to charac-1 Laboratory of Immunology, Faculty of Mediterize the variation of the TNF-a promotor region in 124 unrelated Tunisian pacine Monastir, Monastir, Tunisia.tients with malignant tumors (non-Hodgkin's lymphoma, breast carcinoma, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
2
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 30 publications
7
79
2
3
Order By: Relevance
“…The less common allele, G-308A, was actually too rare in the present data sets to provide adequate statistical power for investigation. The frequency of the -308A allele was 1.3% (n ϭ 240) in this study and 1.7% (n ϭ 575) in another Japanese study [13], 3.1% (n ϭ 113) in Koreans [9], 7.4% (n ϭ 121) in Chinese [27], and 16.5% in Tunisia [26]. The TNF-A -857T allele is not rare, and its frequency seems to be similar among ethnic groups; 17.0% (457/2690) in this study, 17.3% (n ϭ 575) in another study in Japan [13], and 23.2% (n ϭ 235) in Northern Ireland [28].…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The less common allele, G-308A, was actually too rare in the present data sets to provide adequate statistical power for investigation. The frequency of the -308A allele was 1.3% (n ϭ 240) in this study and 1.7% (n ϭ 575) in another Japanese study [13], 3.1% (n ϭ 113) in Koreans [9], 7.4% (n ϭ 121) in Chinese [27], and 16.5% in Tunisia [26]. The TNF-A -857T allele is not rare, and its frequency seems to be similar among ethnic groups; 17.0% (457/2690) in this study, 17.3% (n ϭ 575) in another study in Japan [13], and 23.2% (n ϭ 235) in Northern Ireland [28].…”
Section: Discussionsupporting
confidence: 44%
“…The finding that IL-1B C-31T was associated with H. pylori seropositivity [4][5][6][7] prompted us to examine TNF-A and TNF-B polymorphisms. The documented associations between TNF polymorphisms and several diseases [13,[26][27][28][29] indicate that these polymorphisms are functional or that they are linked with a functional polymorphism, and this feature was also part of the rationale for the present study.…”
Section: Discussionmentioning
confidence: 81%
“…Associations in several cancers including breast, liver, and gastric cancers have also been reported (Chouchane et al 1997;Mestiri et al 2001;Jeng et al 2008;Shibata et al 2009). The most commonly examined polymorphism is the PstI polymorphism in nucleotide 1267 of HSPA1B (rs1061581).…”
Section: Introductionmentioning
confidence: 81%
“…Although we did not measure circulating TNF-α levels, TNF-α-308*A allele has already been shown to increase the constitutive and inducible expression of TNF-α protein, possibly caused by the differential binding of a nuclear protein to the TNF-α-308*A allele (Kroeger et al, 1997;Wilson et al, 1997). It has been reported that some malignant tumors such as prostate cancer, nonHodgkin's lymphoma and breast carcinoma are related to TNF-α-308*A/G gene polymorphism (Chouchane et al, 1997;Oh et al, 2000;Jeng et al, 2007). Our result shows that TNF-α-308*A/G gene polymorphism is not related to hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%